PENGARUH MEDIA PEMBELAJARAN (POJOK BACA) TERHADAP PEMAHAMAN MEMBACA SISWA KELAS III SD NEGERI BINTARO 02 JAKARTA SELATAN - Lutfi; Aribah, Hafidah (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
Reading ability is one of the basic skills that is very important for students. However, students' interest in reading nowadays tends to decline. One of the efforts to increase students' interest in reading and reading comprehension is to provide interesting learning media, such as reading corners. The reading corner is expected to create a pleasant learning environment and motivate students to read more often. This study aims to determine the effect of using a reading corner on improving the reading comprehension of third grade students. Specifically, this study wanted to measure the extent to which students' reading comprehension improved after using the reading corner in learning. The effect of the media (reading corner) was given to class III in the reading comprehension process at SD Negeri Bintaro 02 in the 2024/2025 school year. The research method used was the experiment method, which involved 62 students. Data collection was carried out using instruments and question grids in the form of pretests and posttests which had been declared valid and reliable. The results of students' reading comprehension have met the pre-requisite test of hypothesis testing analysis. The results showed that there was an effect of media (reading corner) in improving students' reading comprehension in class III SD Negeri Bintaro 02. Normality test using Liliefors test. Homogeneity test using Fisher test the calculation results obtained Fhitung 1.013 ≤ Ftabel 0.377 then Ho is accepted, meaning that the two groups of data have the same variance or homogeneous. Hypothesis testing using t-test obtained Thitung then Ho is rejected and H1 is accepted. Therefore, the results of this study conclude that there is an effect of media (reading corner) on students' reading comprehension. The results of this study are expected to contribute to the world of education. Especially in an effort to improve reading comprehension for students.